Qur'anic Education and Qira'at Methodology: Revealing the Characteristics of Imam Al-Bazy's Qira'at Shadzah in the Context of Learning - Hafid, Abdul Hamid; Nabilah, Is’ad Durrotun; Najakhah, Vina Umdatun (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study explores the unique characteristics of Al-Bazy's recitation path, specifically focusing on the recitation of the takbir after Surat Al-Duha until the end of the Qur'an. This Takbir, although considered weak by hadith scholars, is well-known among Qurra' and has a sanad that goes back to the Prophet Muhammad. This study identified three main types of Ta'at al-Bazy: 1) Ta'at beginning with madd letters (elongated vowels), 2) Ta'at with a correct sukun consonant, and 3) Ta'at that begins with a harakat. In addition, Al-Bazy's recitation differs from other scholars in terms of the lengthening of the letter